2005
DOI: 10.1039/b417384h
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities of crystal faces of aragonite (CaCO3) compared by atomic force microscopic observation of facet formation processes in aqueous acetic acid

Abstract: Crystal faces of aragonite in various orientations were dissolved in water or in a dilute aqueous acetic acid. Facet formation processes were observed in situ using atomic force microscopy (AFM). At the polar (001) surface, which gave atom-resolved AFM images in air, less polar {112} facets were developed in water. At two other polar faces (110) and (010), which are frequently seen in natural forms, electrically neutral facets such as (130) and (100) were developed in the acidic solution. No facet formation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Among the crystal faces intersecting with the c-axis, the {1 1 2} facets were formed during the dissolution of polar (0 0 1) face of aragonite in the acidic condition [6,7]. This face is observed in natural forms A2 of aragonite and S2 of strontianite in Fig.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Among the crystal faces intersecting with the c-axis, the {1 1 2} facets were formed during the dissolution of polar (0 0 1) face of aragonite in the acidic condition [6,7]. This face is observed in natural forms A2 of aragonite and S2 of strontianite in Fig.…”
Section: Introductionmentioning
confidence: 93%
“…One of the authors studied facet formation processes at the polar aragonite faces with AFM during dissolution in dilute aqueous acetic acid [6,7], and found that the polar faces were replaced with the neutral facets. The changes in the relative stabilities of the crystal faces were explained, as is demonstrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We have compared relative stabilities of aragonite (CaCO 3 ) faces in dilute aqueous acetic acid and have found that the equilibrium form of the crystal in the acidic condition should be totally different from natural forms, probably obtained in alkaline environments [1,2]. Protonation of carbonate ions changes charge distributions at the surfaces.…”
Section: Introductionmentioning
confidence: 98%
“…Apparently polar crystal faces of aragonite are stabilized by neutralization of positive charges of Ca 2 + on the top layer, by the negative charges of O atoms pointing out of the carbonate layer at lower levels [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, one of the authors compared stabilities of crystal faces of the aragonite (CaCO 3 ) by observing the facet formation in etch pits during the dissolution of the crystal faces with AFM [7,8]. In an acidic solution, the (1 0 0) face which does not appear in natural crystal forms was stabilized and became atom-flat.…”
Section: Introductionmentioning
confidence: 98%